OP0310 Association of Neutrophil Extracellular Traps with Atherosclerosis in Rheumatoid Arthritis. (15th July 2016) - Barbarroja, N.; Ruiz-Limόn, P.; Perez-Sanchez, C.; Jimenez-Gomez, Y.; Abalos-Aguilera, M.C.; Arias de la Rosa, I.; Segui, P.; Font, P.; Aguirre, M.A.; Calvo, J.; Ortega, R.; Castro, M.C.; et al.
Abstract : Background: Neutrophil extracellular traps (NETs) have recently been implicated in vascular damage and atherothrombosis. Extruded DNA fibers containing multiple proinflammatory and thrombotic molecules induce the activation and recruitment of monocytes and dendritic cells to the vessel wall. Enhanced NETosis occurs in rheumatoid arthritis (RA), which has been shown related to the pathogenesis of this disorder. However, the relevance of this abnormality in the development of atherosclerosis has not been elucidated yet. Objectives: To evaluate the association of netosis-derived products with the development of atherosclerosis in RA. Methods: One hundred RA patients and 30 healthy donors were included. Carotid intima media thickness (CIMT) was used as atherosclerosis marker. Inflammatory and prothrombotic molecules, nitric oxide (NO), total antioxidant capacity (TAC) and protein nitration (NTyr) were analyzed in plasma. Neutrophils were isolated from RA patients and controls. Spontaneous and induced NETs formation from RA and control neutrophils was assessed in vitro through fluorescence microscopy. Oxidative stress status (JC1 and DCFH) and myeloperoxidase (MPO), neutrophil elastase (NE) protein expression were measured in neutrophils through flow cytometry. Cell-free DNA plasma levels were analyzed using Sytox staining. mRNA expression of peptidyl arginine deiminase 4 (PAD4) was analyzed in neutrophils by RT-PCR. Receiver operator characteristic (ROC) curves were calculated. Results: Induced NETosis was increased in RA patients alongside MPO and NE protein expression in neutrophils. Cell-free DNA plasma levels were found significantly increased in RA patients. ROC curve analysis showed an area under the curve (AUC): 84, with a high sensitivity (69%) and specificity (86%). Those DNA levels strongly correlated with clinical parameters such as evolution time, DAS28, CRP and ESR and autoimmunity state (RF and anti-CCPs levels). In addition, high levels of cell-free DNA were associated with elevated levels of IL-6, MCP-1, spSelectin and tPA in plasma. Moreover, high levels of cell-free DNA correlated with increased NTyr and TAC and decreased NO. At cellular level, cell-free DNA plasma levels correlated with increased oxidative status in RA neutrophils (JC1 and DCFH) and mRNA expression of PADI4. Those patients having pathologic CIMT showed increased cell-free DNA plasma levels (ROC curve analysis: AUC 77, sensitivity 60%, specifity 72%). Conclusions: 1) Elements associated with the extrusion of NETs are significantly enhanced in RA compared with healthy controls. 2) NETosis-derived products, such as cell-free DNA strongly correlated with clinical parameters, inflammatory and oxidative status in RA patients. Thus, NETosis-derived products demonstrated diagnostic potential for atherosclerosis, which might be a complementary tool to discriminate between normal and pathologic CIMT in RA patients. Acknowledgement: Funded by CTS7940, PI2013–0191, PI15/01333, CP15/00158. Disclosure of Interest: None declared